2013
DOI: 10.1128/aem.01703-13
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants forn-Butanol Tolerance in Evolved Escherichia coli Mutants: Cross Adaptation and Antagonistic Pleiotropy betweenn-Butanol and Other Stressors

Abstract: bCross-tolerance and antagonistic pleiotropy have been observed between different complex phenotypes in microbial systems. These relationships between adaptive landscapes are important for the design of industrially relevant strains, which are generally subjected to multiple stressors. In our previous work, we evolved Escherichia coli for enhanced tolerance to the biofuel n-butanol and discovered a molecular mechanism of n-butanol tolerance that also conferred tolerance to the cationic antimicrobial peptide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…Stronger NaCl selection could disfavor mutations that also improve n-butanol resistance, as it is reasonable to expect that different levels of osmotic stress select for distinct tolerance mechanisms. n-Butanol tolerance is also not always associated with improved osmotic stress resistance in evolved mutants (28), so there are at least some evolutionary paths on both the NaCl and n-butanol landscapes that lead to divergent tolerance phenotypes. The overall lack of significant cross-adaptation for the isolates in this case does indicate that specialist mutants with adaptations specific only to NaCl tolerance are favored under these evolutionary conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger NaCl selection could disfavor mutations that also improve n-butanol resistance, as it is reasonable to expect that different levels of osmotic stress select for distinct tolerance mechanisms. n-Butanol tolerance is also not always associated with improved osmotic stress resistance in evolved mutants (28), so there are at least some evolutionary paths on both the NaCl and n-butanol landscapes that lead to divergent tolerance phenotypes. The overall lack of significant cross-adaptation for the isolates in this case does indicate that specialist mutants with adaptations specific only to NaCl tolerance are favored under these evolutionary conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to osmotic stress is known to affect other phenotypes of industrial interest, such as n-butanol or low pH tolerance (17,28) and growth at elevated temperatures (29). Growth assays of the mutants in the presence of inhibitory levels of glucose, 0.8% n-butanol, mild acidic pH, and thermal stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of tolerance (T) was calculated using equation 1 (61). This parameter was calculated using the measured growth parameters (OD 600 ) after 6 and 24 h. In addition, the percentage of inhibition (I) and the relative fitness coefficient (s) were calculated using equations 2 and 3, respectively (62). These parameters were calculated using the measured maximum specific growth rate ( max ) of each strain, which was determined during early exponential growth according to equation 4.…”
Section: Methodsmentioning
confidence: 99%
“…To maintain homeostasis and optimize the use of resources, host microbes activate several genetic programs in response to changing environmental conditions [5][6][7][8][9][10]. Previous studies have shown that the microbial response to alcohol toxicity is not universal but varies according to the host microbe and the type of alcohol [8][9][10][11][12][13][14]. Understanding the nature and dynamics of the host response to specific alcohols is essential for designing effective metabolic and process engineering solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to isobutanol, 1-butanol (or n-butanol) remains a promising biofuel (and chemical commodity). Yet, it is one of the most toxic alcohols due to its elevated hydrophobicity (relative to other alcohols) [15], and its toxicity is strain-dependent [8][9][10][11][12][13]. Despite significant advances, many details regarding the mode of action of different alcohols as well as the nature and adaptation mechanism to alcohol exposure are still being resolved.…”
Section: Introductionmentioning
confidence: 99%